2020
DOI: 10.1136/rapm-2020-101582
|View full text |Cite
|
Sign up to set email alerts
|

Influence of inpatient opioid consumption on persistent use following total knee arthroplasty

Abstract: BackgroundTotal knee arthroplasty (TKA) is associated with a high incidence of continued opioid use beyond the expected period of recovery. The aim of this study was to determine the influence of inpatient opioid consumption on the development of persistent use.MethodsOpioid-naïve patients undergoing primary, uncomplicated TKA were included in a prospective, observational study at a single institution. Postoperatively, opioids were prescribed by orthopedic advanced practitioners or resident physicians and admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Lack of standardisation across prescribing patterns, definition of opioids and usage, and variability in recording periods makes direct comparisons between studies difficult. Rates of persistent opioid use range from 17% at 6 weeks [13] to 7.6% at 12 months [3] and up to 21% at 2 years postoperatively [14]. A recent systematic review from Europe covering eight countries demonstrated opioid use after 3–6 months between 7.9% and 41% after lower limb arthroplasty [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lack of standardisation across prescribing patterns, definition of opioids and usage, and variability in recording periods makes direct comparisons between studies difficult. Rates of persistent opioid use range from 17% at 6 weeks [13] to 7.6% at 12 months [3] and up to 21% at 2 years postoperatively [14]. A recent systematic review from Europe covering eight countries demonstrated opioid use after 3–6 months between 7.9% and 41% after lower limb arthroplasty [15].…”
Section: Discussionmentioning
confidence: 99%
“…studies difficult. Rates of persistent opioid use range from 17% at 6 weeks[13] to 7.6% at 12 months[3] and up to 21%…”
mentioning
confidence: 99%
“…32,35 Alcohol use is also associated with increased postoperative opioid use in TKA patients. 31,36 One study also demonstrated marijuana use as a significant risk factor for prolonged postoperative opioid use. 37…”
Section: Postoperative Prescription Characteristicsmentioning
confidence: 99%
“…12 13 However, recent evidence does not suggest a linkage in opioid-naïve patients undergoing total knee arthroplasty. 14 In those who have been diagnosed with OUD, treatment of pain with most full opioid agonists, such as oxycodone or morphine, puts already vulnerable patients at risk for recurrence or worsening of their active OUD. 12 13 US Food and Drug Administration (FDA)-approved medications for OUD include methadone, buprenorphine, and naltrexone, all of which have been found to be similar with respect to effectiveness, 15 16 with the caveat that the efficacy of naltrexone is comparable (in the short term) only if patients withdraw and abstain from opioid use for 7-10 days prior to initiation of therapy.…”
Section: Special Articlementioning
confidence: 99%